Karakteristik dan Metodologi Tafsir Al-Mizan Al-Thabathaba’i - Rangga Oshi Kurniawan; Aliviyah Rosi Khairunnisa (Jurnal Iman dan Spiritualitas, 2021)
Tafsir is a science that is very important for Muslims to learn when they want to know the meaning of the contents of the Koran verses. The product that is produced when interpreting the Koran is called the tafsir book. As for the person who interprets the Koran, it is called Mufassir. One of the Shi'i descent mufassirs named Muhammad Husain Thabathaba'i, or known as Thabathaba'i is the book Tafsir Al-Mizan Fi Tafsir Al-Qur'an or abbreviated as Tafsir Al-Mizan. He compiled this interpretation based on the request of his students at the University when he taught to collect the materials he had introduced into a book of commentaries. This interpretation uses the tahlili method with the bil ra'yi interpretation approach and is characterized by theology or philosophy. It can be said that this interpretation tends to be fanatical towards the Shi'a group even though Tabataba'i himself compared it with the Sunni group. This interpretation is also known by using the Quran's method, namely interpreting a verse of the Koran with another verse of the Koran. He believes that verses are related to one another. This interpretation is worthy of being used as a reference for readers compared to other commentary books.